Hidden in a daylight - Mytkowska, Joanna; Fundacja Galerii Foksal (Warszawa : Fundacja Galerii Foksal, 2003)
Artists: Paweł Althamer, Cezary Bodzianowski, Christoph Büchel, Jeremy Deller, Jeanne Faust, Omer Fast, Mark Leckey & Donatella, Mark Lewis, Rosalind Nashashibi, Anna Niesterowicz, Enrique Metinides, Paulina Okowska, Mathilde Rosier, Wilhelm Sasnal, Piotr Uklański, Artur Zmuewski
This catalogue is published ... in conjunction with the exhibition ... 17-27 July 2003, organzied in collaboration with the 3rd Film Festival Era New Horizons in Cieszyn, Gutek Film
Polish and English
boek